NARRATIVE IDENTITY OF A GIFTED CHILD OF A YOUNGER AGE - Gudzovskaya, A.A.; Bodyagina, N.V.; Safonova, M.V. (Modern Psychology, 2019)
Gifted children, along with their exceptional abilities, have a number of characteristics that distinguish them from normally developing children. The purpose of the study is to identify the characteristics of the narrative identity of intellectually gifted children. The participants of the study have been 50 children age 7 - 8. To analyze the content 10 categories are used: analytical categories of T. Kuhn, L. Vygotsky, P. Blonsky, R. Burns, R. Nisbett. Gifted children tend to compare themselves to other people and emphasize their own uniqueness. The narrative identity of gifted children is more complex, differentiated by self-esteem. Self-esteem of a gifted child is being developed in comparison with adults, "ideal" people. As a result a child begins to doubt him/herself. Comparative analysis of quantitative and qualitative indicators of narrative texts allowed to consider giftedness as a significant factor that influence self-perception and formation of the narrative identity of a child.
Keywords: gifted child; identity; narrative Identity; individualistic/collectivistic orientation; self-esteem; cognitive complexity